Analysis of the Enem editions in the area of Mathematics and its Technologies (2012 - 2021) (Research, Society and Development, 2022)
The article presents an analysis of the Enem editions carried out from 2012 to 2021, whose objective was to verify the level of coverage of the contents related to the area of Mathematics and its Technologies in relation to the High School curriculum, examining if the contents covered have been sufficient to evaluate the teaching of mathematics in this teaching modality. The qualitative research investigated official documents of Basic Education and the consolidated academic productions (articles and dissertations), as well as the analysis of the Enem exams and didactic collections approved by the National Program of Books and Didactic Materials. The results indicate that the contents of High School are rarely covered and the distribution of questions does not occur homogeneously among the contents evaluated. Thus, it is suggested that the number of questions corresponding to the final three years of Basic Education be expanded, including new content in the Enem Matrix. Another relevant action would be the distribution of problem-situations more evenly among the objects of knowledge and expansion of the evaluation of the scarcer contents.